Constitutional transformations in France at the beginning of the 21st century - Maslovskaya, Tatiana S. (Journal of the Belarusian State University. Law, 2024)
The article examines the experience of constitutional reforms in the France at the beginning of the 21st century. The constitutional reforms carried out in 2000, 2003, 2005, 2007 and 2008 are briefly analysed. Close attention is paid to the constitutional reforms proposed by the presidents of the country. The main vectors of the modern period of constitutional development of France are determined, as well as the most important directions of the proposed constitutional changes of the last ten years.
Keywords: constitution; constitutional transformations; constitutional development; the Fifth Republic; France